The Effect of Communication and Motivation on Employee Performance at PT. Federal International Finance (FIFGROUP) Hertasning Post - Lina Mariana; Muh. Ramli (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The purpose of this study was to determine the effect of communication and motivation on the performance of employees of PT. Federal International Finance (FIFGROUP) Pos Hertasning. The types of data used in this study are primary data and secondary data. The data analysis method used is statistical analysis method in the form of multiple regression analysis, correlation coefficient and coefficient of determination. The results of this study indicate that linear regression, correlation coefficient (r) coefficient of determination (r2) =, t-test and F-test with arithmetic results f-count < f-table so that it can be seen that there is a significant positive relationship between communication and motivation on employee performance at PT. Federal International Finance (FIFGROUP) Pos Hertasning.